Contribution to the Discussion about Innovativeness in the European Union - Rafał KLÓSKA (Communications of International Proceedings, 2021)
The article describes the importance of innovation in the economy and shows the growing role in dynamising the economy. The importance of the issue of innovation in the territorial aspect was emphasized. In terms of innovation, the Polish economy occupies a far-off position among EU countries and requires evolutionary changes.
Keywords: Innovations; European Union.